NARRATIVES OF INSCRIPTIONS ON MEMORIAL PLATES OF JEWS, RUSSIANS, LATVIANS AND LATGALIANS: MEMORY CULTURE DISCOURSE - Senkāne, Olga (Via Latgalica, 2010)
Linguistic execution and narrative structure of the memorial plaques demonstrates not only ideology, axiology etc. of certain ages, culture of memory as such, but also trends in linguistic applications, with respect/without respect to the state language policy representing the respective historical stage (period of the first Latvian independent state, Soviet times, years of the third awakening and independence). The language/languages used in narratives of memorial plaques in the Rēzekne City, structure and content of the narratives depends on 1) location of the memorial plaque (cemetery, city sights, downtown or outskirts, etc.) 2) time period for installation of the memorial plaque (periods of independence/Soviet times), 3) national/religious affiliation of the dead/killed, 4) the pathos to be achieved (patriotic, heroic, philosophical, ritual, etc.).Monolingual memorial plaques in Latvian or bilingual memorial plaques (in Latvian and Russian) constitute the largest quantity in Rēzekne. During the independence periods these are mostly devoted to: 1) politicians, public and culture figures, clergy (8), 2) Latvian/Latgalian freedom fighters, warriors (3), 3) victims of the Holocaust and the communist terror (3). During the Soviet period a special focus is on the World War II fighters against fascism and the victims of fascism, as well as some prominent cultural figures of socialist era – directors, specialists in literature, artists (11).Memorial plaques installed before June 1940 are monolingual; plaques installed from WW II to 1989 are bilingual; plaques installed or renovated during the period when Latvia regained national independence are monolingual (in Latvian or Latgalian) or multilingual (in Russian, Latvian, English and German).Inscriptions of the Soviet-era memorial plaques (predominantly in Russian and Latvian) are dominated by heroic pathos, which is based in the respective ideology; in inscriptions of the independence time a tone of patriotism and religious rituals is topical, as well as there is also considerable use of the language diversity (utilization of Latgalian and English). Jewish memorial plaques installed during recent years of independence to the Holocaust victims, usually are in 3-4 languages (in Latvian, Yiddish, Russian and English). Text of memorial plaques in multiple languages may be slightly different (choice of lexemes) while maintaining the overall low-key pathos.The Jewish Holocaust memorial plaques are one of the few multilingual signs in Rēzekne. Order of inscriptions in 3 or 4 languages enables to reason about the hierarchy of languages during the Soviet era and the years of independence, at the beginning of 21st century. In trilingual signs of the Soviet-era plaques Latvian language is featured as the last one – after Yiddish and Russian, while the plaque installed in 2006 already represents different layout hierarchy indicating the prevailing role of Latvian as the official language where the victims’ mother tongue moves to the second position, but Russian in memorial plaques is still more important than English. Layout and stylistics of the narrative in this memorial plaque inscription is seemingly neutrally informative (where, when, who, did what), but contains moderate dramatic qualities, modest reminder of active participation of the locals in extermination of Jews. The inscription can represent the direction of narration in the memory culture of the Holocaust victims: inscriptions have a reminiscent, recapturing function (so the recipient needs preliminary knowledge), therefore they lack emotionality and the dramatic qualities, evaluative style resources, unlike the Jewish tombstone inscriptions.Latgalian memorial plaques in Rēzekne are still rare, total number of them are five and they are falling mainly within the religious (Catholic identity) discourse, largely devoted to prominent Latgalian clergy, the clergy patrons, the victims of communist terror. These memorial plaques in terms of narrative expansion of the inscriptions are not focused on reminder or reconstruction as it is, for example, in the inscriptions on plaques of the Holocaust victims, and are performing another important function of narrative – creating memory (knowledge) for those who lack it, providing a ready-made, educational, observational, emotional assessment – this is a very important feature of the Latgalian memorial plaques. Inscription narratives show respect to an addressee without knowledge, therefore subtexts are not intended there.National and territorial identity of Latgale in the historical and contemporary perspective is featured by the syncretism of cultures. Use of languages on the inscriptions of Rēzekne memorial plaques is indicative of the existence of multilingual environment the least respect for which is shown during the first Latvian independence (1818–1940) and also during the restoration of independence period, as most of the Soviet-era plaques renovated in 90ies of the 20th century and early 21st century now are monolingual (in Latvian), but at the time of installation (50–70ies of the 20th century) they have been mostly bilingual (in Latvian, in Russian) or made only in Russian. Today, after regaining independence, the Latvian prevails in the multilingual urban landscape, the Russian still is quite enduring (especially in the outskirts of town), Latgalian is gradually moving away from formal constraints, and revived, but the Jewish is irretrievably withering away. Unfortunately, culture of memories in format of Hebrew memorial plaques and tombstone inscriptions will soon be the only lingual evidence of the existence of this historically so important element of the regional identity.